Assessing Operating Efficiency Gains from Hypothetical Mergers and Acquisitions in the Gulf Cooperation Council Banking Sector: Evidence from a Cross-Regional Analysis - Lootah, Ahmad Majid Ahmad Nasser; Zervopoulos, Panagiotis D.; Al Tamimi, Hussein A. Hassan (International Journal of Economics and Financial Issues, 2025)
This study examines whether hypothetical mergers and acquisitions (M&As) among banks in the Gulf Cooperation Council (GCC) region can enhance their efficiency relative to that of banks in the European Union (EU), Turkey, and the Middle East and North Africa (MENA). Using a Bayesian data envelopment analysis (DEA) approach, bias-corrected efficiencies and the degree of operating efficiency gains (DOEG) are calculated for the proposed M&A scenarios. The sample includes 42 of the largest GCC banks by asset size, alongside 55 EU and Turkish banks and 31 MENA-based banks. The analysis covers the period from 2018 to 2020. The adoption of the novel Bayesian DEA method ensures robust and valid findings. This study also addresses an understudied topic: the potential impact of M&A activity in the GCC on the performance and competitiveness of consolidated banks compared to those of EU, Turkish, and MENA banks. The results suggest that M&As are likely to benefit consolidated GCC banks within the region. However, mergers involving both efficient and inefficient GCC banks are not expected to significantly enhance their performance when compared to their counterparts in the EU, Turkey, and MENA regions.